2019
DOI: 10.1104/pp.19.00632
|View full text |Cite
|
Sign up to set email alerts
|

ABA-Induced Sugar Transporter TaSTP6 Promotes Wheat Susceptibility to Stripe Rust

Abstract: Biotrophic pathogens, such as wheat rust fungi, survive on nutrients derived from host cells. Sugar appears to be the major carbon source transferred from host cells to various fungal pathogens; however, the molecular mechanism by which host sugar transporters are manipulated by fungal pathogens for nutrient uptake is poorly understood. TaSTP6, a sugar transporter protein in wheat (Triticum aestivum), was previously shown to exhibit enhanced expression in leaves upon infection by Puccinia striiformis f. sp. tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 82 publications
(117 reference statements)
2
52
0
Order By: Relevance
“…Biotic stresses such as pathogen infection can also modulate ABA homeostasis in host plants. Some biotrophic pathogens such as wheat rust fungi can promote increases in ABA that lead to elevated cytoplasmic sugar accumulation by enhancing TaSTP6 expression (Huai et al 2019). Upon infection by the necrotrophic pathogen Botrytis cinereal , the transcription factor WRKY33 promotes ABA biosynthesis by upregulating the transcription of NCED3 and NCED5 in Arabidopsis (Liu et al 2015a).…”
Section: Metabolic Control Of Aba Levelsmentioning
confidence: 99%
“…Biotic stresses such as pathogen infection can also modulate ABA homeostasis in host plants. Some biotrophic pathogens such as wheat rust fungi can promote increases in ABA that lead to elevated cytoplasmic sugar accumulation by enhancing TaSTP6 expression (Huai et al 2019). Upon infection by the necrotrophic pathogen Botrytis cinereal , the transcription factor WRKY33 promotes ABA biosynthesis by upregulating the transcription of NCED3 and NCED5 in Arabidopsis (Liu et al 2015a).…”
Section: Metabolic Control Of Aba Levelsmentioning
confidence: 99%
“…In addition, to further determine whether TaSTP13 forms hetero-oligomers with other STPs from wheat, interactions between TaSTP13 and TaSTP6, a STP conferring enhanced wheat susceptibility to stripe rust [20], were studied in yeast and tobacco plants as described above. The results showed that TaSTP13 could not interact with TaSTP6 (data not shown), indicating that TaSTP13 possibly functions as a homo-oligomer.…”
Section: Oligomerization Of Tastp13mentioning
confidence: 99%
“…The infection sites in stained tissues were examined using an Olympus BX-51 microscope (Olympus, Tokyo, Japan) and measured with the cellSens Entry software (Olympus, Tokyo, Japan). Data of each index were obtained as described previously [20]. For the statistical analyses, standard deviations, one-way ANOVA and t-test were performed using SPSS software v17.0 based on three independent samples.…”
Section: Histological Observation Of Fungal Growthmentioning
confidence: 99%
See 2 more Smart Citations